2016
DOI: 10.1371/journal.pone.0168501
|View full text |Cite
|
Sign up to set email alerts
|

A Novel HRAS Mutation Independently Contributes to Left Ventricular Hypertrophy in a Family with a Known MYH7 Mutation

Abstract: Several genetic conditions can lead to left ventricular hypertrophy (LVH). Among them, hypertrophic cardiomyopathy (HCM), caused by mutations in sarcomere genes, is the most common inherited cardiac disease. Instead, RASopathies, a rare class of disorders characterized by neuro-cardio-facial-cutaneous abnormalities and sometimes presenting with LVH, are caused by mutations in the RAS-MAPK pathway. We report on a 62-years-old male who presented isolated severe obstructive LVH but did not carry the sarcomere mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The WES approach enables studies of the patients within an environmental and clinical context through large-scale cohort trials and data processing with a focus on the associations among molecular biology, disease and health phenotypes to assure a more accurate diagnosis, leading to the establishment of individualized disease prevention and treatment programmes (Tetreault et al, 2015; Collins et al, 2016; Tebani et al, 2016). Moreover, WES has allowed the identification of new genes associated to the clinical description of patients with RASopathies (Niguidula et al, 2018; Matias et al, 2019), such as RIT1 (Aoki et al, 2013), A2ML1 (Vissers et al, 2015), RASA2, SPRY1 (Chen et al, 2014), SOS2, LZTR1 (Yamamoto et al, 2015; Umeki et al, 2019), PPP1CB (Gripp et al, 2016), CBL (Coe et al, 2017), and MRAS (Higgins et al, 2017), as well as new mutations in genes of the RAS/MAPK pathway (Carapito et al, 2014; Sana et al, 2016; Coe et al, 2017; Harms et al, 2018; Valera et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The WES approach enables studies of the patients within an environmental and clinical context through large-scale cohort trials and data processing with a focus on the associations among molecular biology, disease and health phenotypes to assure a more accurate diagnosis, leading to the establishment of individualized disease prevention and treatment programmes (Tetreault et al, 2015; Collins et al, 2016; Tebani et al, 2016). Moreover, WES has allowed the identification of new genes associated to the clinical description of patients with RASopathies (Niguidula et al, 2018; Matias et al, 2019), such as RIT1 (Aoki et al, 2013), A2ML1 (Vissers et al, 2015), RASA2, SPRY1 (Chen et al, 2014), SOS2, LZTR1 (Yamamoto et al, 2015; Umeki et al, 2019), PPP1CB (Gripp et al, 2016), CBL (Coe et al, 2017), and MRAS (Higgins et al, 2017), as well as new mutations in genes of the RAS/MAPK pathway (Carapito et al, 2014; Sana et al, 2016; Coe et al, 2017; Harms et al, 2018; Valera et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The role of FDPS in cardiac homeostasis 447 model [17], and a dominant-negative Ras mutation protects against ventricular remodeling in response to pressure overload [25]. Additionally, a mutation that resulted in constitutive activation demonstrated that H-Ras can exacerbate pathological cardiac hypertrophy [26]. Moreover, the use of simvastatin or carabin to interfere with Ras signaling ameliorated cardiac hypertrophy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, diabetic children have significant changes in LV dimensions, and girls are more affected than boys ( 55 ). Finally, there is strong evidence for the genetic influence on LVH prevalence across several study designs, datasets and ethnicities ( 56 60 ), and several genetic conditions, i.e., hypertrophic cardiomyopathy, caused by mutations in sarcomere genes ( 61 ), and RASopathies are causally associated with LVH ( 62 ). However, specific genetic influences on prevalence of HTN-associated LVH are currently unknown.…”
Section: Detection Methodsmentioning
confidence: 99%